Biostimulation of Bacteria in Liquid Culture for Identification of New Antimicrobial Compounds - Hooman Mirzaee; Emily Ariens; Mark A. T. Blaskovich; Richard J. Clark; Peer M. Schenk (MDPI AG, 2021)
We hypothesized that environmental microbiomes contain a wide range of bacteria that produce yet uncharacterized antimicrobial compounds (AMCs) that can potentially be used to control pathogens. Over 600 bacterial strains were isolated from soil and food compost samples, and 68 biocontrol bacteria with antimicrobial activity were chosen for further studies based on inhibition assays against a wide range of food and plant pathogens. For further characterization of the bioactive compounds, a new method was established that used living pathogens in a liquid culture to stimulate bacteria to produce high amounts of AMCs in bacterial supernatants. A peptide gel electrophoresis microbial inhibition assay was used to concurrently achieve size separation of the antimicrobial peptides. Fifteen potential bioactive peptides were then further characterized by tandem MS, revealing cold-shock proteins and 50S ribosomal proteins. To identify non-peptidic AMCs, bacterial supernatants were analyzed by HPLC followed by GC/MS. Among the 14 identified bioactive compounds, 3-isobutylhexahydropyrrolo[1,2-a]pyrazine-1,4-dione and 2-acetyl-3-methyl-octahydropyrrolo[1,2-a]piperazine-1,4-dione were identified as new AMCs. Our work suggests that antimicrobial compound production in microbes is enhanced when faced with a threat from other microorganisms, and that this approach can rapidly lead to the development of new antimicrobials with the potential for upscaling.